Early life stress and functional connectivity in antipsychotic-naïve first episode psychosis patients - Hillary N. Patton; Jose O. Maximo; James E. Bryant; Adrienne C. Lahti (Schizophrenia)
Abstract The neural mechanisms underlying the association between childhood trauma (CT) and psychosis spectrum disorders remains unclear. The objective of this study is to examine the relationship between childhood trauma and functional connectivity of fronto-limbic regions in a large sample of antipsychotic-naïve patients with first episode psychosis (FEP). Resting state fMRI data from 105 FEP patients and 123 healthy controls (HC) were used. Our regions of interest included bilateral hippocampus/amygdala and ventromedial prefrontal cortex (vmPFC). Childhood Trauma Questionnaire (CTQ) total and subscale scores were correlated with the resting state functional connectivity (rsFC) data. Partial correlation analyses indicated that higher CTQ sexual abuse subscale scores in FEP patients were associated with increased left amygdala—vmPFC rsFC (r(59) = 0.27, p < 0.05) and higher CTQ emotional neglect subscale scores in FEP patients were associated with increased left hippocampus—vmPFC rsFC (r(59) = 0.26, p < 0.05). Follow-up analysis showed a significant interaction effect of group (FEP and HC) and CTQ score (sexual abuse subscale) on left amygdala—vmPFC rsFC (β = 0.014, p < 0.05). Higher CTQ sexual abuse subscale scores were associated with increased rsFC in FEP patients (β = 0.56, p < 0.001). but reduced rsFC in healthy controls (β = −0.56, p < 0.001). The results also provide support for the long-term differential impact of trauma subtypes on the human brain. Overall, the results contribute to the understanding of the neural mechanisms underlying the association between childhood trauma and psychosis spectrum disorders.